An analysis of Daniel Kahneman's Thinking, fast and slow - Allan, Jacqueline Anne (London Macat International Ltd., 2017)
Thinking, Fast and Slow by Daniel Kahneman offers a general audience access to over six decades of insight and expertise from a Nobel Laureate in an accessible and interesting way. Kahneman's work focuses largely on the problem of how we think, and warns of the dangers of trusting to intuition - which springs from "fast" but broad and emotional thinking - rather than engaging in the slower, harder, but surer thinking that stems from logical, deliberate decision-making. Written in a lively style that engages readers in the experiments for which Kahneman won the Nobel, Thinking, Fast and Slow's real triumph is to force us to think about our own thinking.
Keywords: Kahneman, Daniel, 1934-.; Thought and thinking